2022
DOI: 10.1017/cts.2022.383
|View full text |Cite
|
Sign up to set email alerts
|

The NJ Alliance for Clinical and Translational Science (NJ ACTS) experience: Responding at “warp speed” to COVID-19

Abstract: Introduction: The COVID-19 pandemic’s need for life-saving treatments and a "warp speed" vaccine challenged the National Institutes of Health’s Clinical and Translational Science Award (CTSA) recipients to improve their methods and processes in conducting clinical research. While CTSA recipient, New Jersey Alliance for Clinical and Translational Science (NJ ACTS), responded to this call to action with significant clinical research milestones, a comprehensive understanding of regulatory metrics during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…The great majority of CRCs responding to our survey participated in COVID-related research efforts, including vaccine trials, noninterventional studies (e.g., biorepositories, serology studies, and diagnostic development), and therapeutic trials. CRC support spanned the spectrum of clinical research activities, including study start-up, regulatory support, training of clinical research staff, and conduct of study visits, confirming earlier reports [ 5 , 11 ]. Participation in noninterventional studies was higher than in therapeutic trials, likely representing lower staffing barriers to conducting noninterventional studies.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The great majority of CRCs responding to our survey participated in COVID-related research efforts, including vaccine trials, noninterventional studies (e.g., biorepositories, serology studies, and diagnostic development), and therapeutic trials. CRC support spanned the spectrum of clinical research activities, including study start-up, regulatory support, training of clinical research staff, and conduct of study visits, confirming earlier reports [ 5 , 11 ]. Participation in noninterventional studies was higher than in therapeutic trials, likely representing lower staffing barriers to conducting noninterventional studies.…”
Section: Discussionsupporting
confidence: 81%
“…Reasons for this included continued safety concerns from participants and investigators and staffing shortages. Many CRCs reported that they mitigated the negative impact on research activities by pivoting to support COVID-related research, maintaining close coordination with institutional entities and investigators, implementing practices to mitigate risks to research personnel, and adopting innovative approaches to supporting clinical research during the pandemic, including eConsent, virtual visits, electronic source documentation, and home delivery of experimental therapeutic agents [1][2][3][4][9][10][11]. These latter approaches allowed outpatient clinical research to resume, but most would not be captured as CRC census.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our colleagues from the New Jersey Alliance for Clinical and Translational Science (NJ ACTS) [4] contribute to a better understanding of regulatory mechanisms during an emergency by identifying and comparing metrics illustrating the efficiency and efficacy of their research mobilization efforts during COVID-19. Their analysis of data from the Institutional Review Board, the Clinical Research Units, and the Office of Research and Sponsored Programs suggests that by rapidly making process improvements and adaptations, their institution effectively responded to challenges posed by the pandemic, including a significant increase in IRB-approved studies in 2020, the enrollment of adult and pediatric participants for COVID-19-related research, study income, and decrease in turnaround time for approval of COVID-19 studies.…”
mentioning
confidence: 99%